Democracia e a educação escolar : uma análise à luz da pedagogia histórico-crítica - Gomes, Juliana Pereira Rageteles (2018)
This paper consists of a theoretical-conceptual study that has as object of analysis the debate about the relations between democracy and schooling. We intend to examine the current political scenario in this country, particularly after the re-election of Dilma Rousseff in 2014, investigating and contextualizing the political circumstances that culminated the president's impeachment in 2016. It endeavors to make clear the democratic split that has characterized as a parliamentary, juridical and mediatic coup surrounded by a presence of hatred and extreme conservatism. In order to comprehend the reasons why the battle for the preservation of democracy in this country is crucial, it is proposed to rescue the origin and development of democracy in history, pointing out its progress over time, emphasizing the ancient model lived by the Greeks; and the modern, within a capitalist society that suggests the exploitation of individuals. We highlight in this inquiry that the full realization of a democratic society is not compatible with capitalist values, therefore, overcoming this model is necessary and education can contribute to this ideal. In this sense, we take the historical-critical education as a theoretical and methodological reference to present the importance of schooling in the formation of new individuals for a new society. For this, we explain the contributions of this educational theory in the conceptions of man, work, educational work and schooling. In order to combine efforts in search of an education that aims at the maximum development of individuals, especially those coming from the working class, we present a critical analysis of the Project "Escola Sem Partido" (In English, “Unpolitical School”, PL 867/2015), revealing such initiative as the utmost antidemocratic expression that threatens schooling in this country. Finally, we focus on movements of resistance that are organized against the advances that aim at the impoverishment and the emptying of public education, the one that admits, mainly, children of the working class. We conclude by affirming the need to fight for the preservation of the public, secular, free and quality school and the right of access of the working class to the broaden knowledge, showing that the greatest act of resistance of the teacher is to insist on teaching, seeking the maximum development of their students.